2012
DOI: 10.1007/s00284-012-0277-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Glyphosate on Potential Pathogens and Beneficial Members of Poultry Microbiota In Vitro

Abstract: The use of glyphosate modifies the environment which stresses the living microorganisms. The aim of the present study was to determine the real impact of glyphosate on potential pathogens and beneficial members of poultry microbiota in vitro. The presented results evidence that the highly pathogenic bacteria as Salmonella Entritidis, Salmonella Gallinarum, Salmonella Typhimurium, Clostridium perfringens and Clostridium botulinum are highly resistant to glyphosate. However, most of beneficial bacteria as Entero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
147
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 231 publications
(173 citation statements)
references
References 48 publications
2
147
1
4
Order By: Relevance
“…The bacterial count was determined using the plating colonies method (Sanders, 2012) on neomycinÁpolymyxin blood agar (neomycin (100 mg/l; Carl Roth)/ polymyxin B (50 mg/l; Sigma-Aldrich). C. perfringens colonies were confirmed by matrix-assisted laser desorption/ionization time-of-flight analysis (Shehata et al, 2013) to ensure specificity and the diagnosis and to exclude misdiagnosis due to contaminating haemolysing bacteria.…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial count was determined using the plating colonies method (Sanders, 2012) on neomycinÁpolymyxin blood agar (neomycin (100 mg/l; Carl Roth)/ polymyxin B (50 mg/l; Sigma-Aldrich). C. perfringens colonies were confirmed by matrix-assisted laser desorption/ionization time-of-flight analysis (Shehata et al, 2013) to ensure specificity and the diagnosis and to exclude misdiagnosis due to contaminating haemolysing bacteria.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was suggested that gastrointestinal disorders, obesity, diabetes, heart disease, depression, autism, infertility, cancer and Alzheimer's disease are associated with Western diet [11]. Furthermore, genotoxic activity [12], teratogenic activity [13], and disturbance of the normal gut bacterial community [14,15] due to glyphosate are reported. Glyphosate showed cytotoxic effects on different cells in vitro [16][17][18], and Barbosa et al [19], proposed that glyphosate may have contributed to the Parkinsonism due to its chemical similarity with glycine, a co-factor required for activation of the N-methyl-d-aspartase (NMDA) receptor, which controls excitatory actions in the central nervous system and is also involved in memory and learning.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study that compared the effects of glyphosate on potential pathogens and beneficial members from poultry, 14 it was reported that most pathogenic bacteria were highly resistant towards the glyphosate, although Campylobacter spp. were susceptible.…”
Section: Discussionmentioning
confidence: 99%